1986
DOI: 10.1007/bf00640919
|View full text |Cite
|
Sign up to set email alerts
|

Barium can replace calcium in calmodulin-dependent contractions of skinned renal arteries of the rabbit

Abstract: Renal arteries of the rabbit were chemically skinned using Triton X-100. In EGTA-buffered solutions containing calmodulin and ATP, small strips of the skinned preparations were found to develop contractile force which was dependent on the concentrations of either free calcium or of free barium. However, a 220 times greater concentration of barium than of calcium was necessary for comparable effects. Quantitatively, the response to barium was dependent on the concentration of calmodulin added to the test soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 6 publications
3
7
0
Order By: Relevance
“…One explanation is that Ba2+ itself may accumulate in endothelial cells at levels sufficient to compensate for the low affinity of Ba2+ for calmodulin, since it is not taken up into intracellular stores or readily removed from the cells. This explanation has also been discussed in previous studies concerning the calmodulindependent contraction of smooth muscle (23,24) and Ca"-ATPase in human erythrocytes (25). Another possibility is that Ba2+ may induce the release of Ca 21 from endothelial intracellular Ca 21 stores, as has been proposed for Ba2+-induced contraction in smooth muscle (24,26).…”
supporting
confidence: 67%
“…One explanation is that Ba2+ itself may accumulate in endothelial cells at levels sufficient to compensate for the low affinity of Ba2+ for calmodulin, since it is not taken up into intracellular stores or readily removed from the cells. This explanation has also been discussed in previous studies concerning the calmodulindependent contraction of smooth muscle (23,24) and Ca"-ATPase in human erythrocytes (25). Another possibility is that Ba2+ may induce the release of Ca 21 from endothelial intracellular Ca 21 stores, as has been proposed for Ba2+-induced contraction in smooth muscle (24,26).…”
supporting
confidence: 67%
“…Although the ½Ba 2þ used in the sensing experiment was 100 times higher than that of ½Ca 2þ , it was still not sufficient to trigger the association of TnI with CaM. These results are in agreement with previous studies showing that the ½Ba 2þ required for CaM activation is approximately 200-fold higher than that for ½Ca 2þ (29,30). Overall, these electrical measurements suggested that the SiNW-FETcan be applied for the investigation of the detailed mechanisms of protein-protein interactions.…”
Section: Supporting Information)supporting
confidence: 88%
“…While Pb has been shown to activate CaM effectively and in fact has a higher affinity than Ca (Fullmer et al, 1985;Richardt et al, 1986;Ouyang & Vogel, 1998), Ba activation requires an around 200-fold higher concentration than Ca for CaM activation (Kreye et al, 1986;Yamazaki et al, 1996). These observations can be explained at least in part by the variations in the ionic radii of these ions and by the differences in metal-ion coordination distances in the EF-hands in the complexes: these would be expected to be reflected in the actual affinity.…”
Section: Discussionmentioning
confidence: 99%